2019
DOI: 10.1007/s00586-019-06227-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression and activity of hyaluronidases HYAL-1, HYAL-2 and HYAL-3 in the human intervertebral disc

Abstract: Purpose Hyaluronic acid plays an essential role in water retention of the intervertebral disc (IVD) and thus provides flexibility and shock absorbance in the spine. Hyaluronic acid gets degraded by hyaluronidases (HYALs), and some of the resulting fragments were previously shown to induce an inflammatory and catabolic response in human IVD cells. However, no data currently exist on the expression and activity of HYALs in IVD health and disease. Methods Gene expression, protein expression and activity of HYALs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…21,22,27,27,28 Recently, Krupkova et al have reported that HYAL1, HYAL2, and HYAL3 were expressed in human IVDs, and that the mRNA expression of HYAL1 and the protein expression of HYAL2 were significantly increased in moderate/severe IVDD samples. 50 Our analysis using immunohistochemistry showed elevated expression of HYAL1, HYAL2, and CEMIP in highly degenerated IVD tissues. The expression of all three molecules, with a significant difference only in HYAL1, showed an increasing tendency in accordance with progression of IVDD.…”
Section: Discussionmentioning
confidence: 65%
“…21,22,27,27,28 Recently, Krupkova et al have reported that HYAL1, HYAL2, and HYAL3 were expressed in human IVDs, and that the mRNA expression of HYAL1 and the protein expression of HYAL2 were significantly increased in moderate/severe IVDD samples. 50 Our analysis using immunohistochemistry showed elevated expression of HYAL1, HYAL2, and CEMIP in highly degenerated IVD tissues. The expression of all three molecules, with a significant difference only in HYAL1, showed an increasing tendency in accordance with progression of IVDD.…”
Section: Discussionmentioning
confidence: 65%
“…Hyaluronidases intracellularly degrade hyaluronan, one of the major glycosaminoglycans of the extracellular matrix (ECM). Hyaluronan is involved in cell proliferation, migration and differentiation and forms a major component of the ECM of cartilage, thus contributing to the structural and functional integrity of the bone [33,34]. Whilst vitamin D increased the expression of HYAL3 in all conditions, the presence of signi cantly higher fold increase found in the GM-treated group alone suggests that vitamin D may play an underappreciated role in regulating the extracellular matrix (ECM) via the MSCs.…”
Section: Results 1α25-(oh) 2 D 3 -Regulates Genes Associated With Hmscs Function and Survivalmentioning
confidence: 99%
“…HYAL1 encodes lysosomal hyaluronidase, which degrades HA in cells. In one study, the gene expression of HYAL1 and the protein expression of HAYL2 were significantly increased in moderate/severe IDD samples compared with those without or with low IDD [ 37 ]. The protein encoded by LYVE1 acts as a receptor and binds to both soluble and fixed HA and may also play a role in lymphatic HA transport.…”
Section: Discussionmentioning
confidence: 99%